PENGARUH KUALITAS PELAYANAN, BRAND IMAGE DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN ( Studi Kasus Gerai Alfamidi Cabang Timoho, Kota Yogyakarta ) - Destiana, Eka; Rinaldi, Rinaldi (Journal Competency of Business, 2023)
This study aims to determine the influence of Service Quality, Brand Image, and Promotion on the Purchasing Decision of the Alfamidi Timoho Yogyakarta branch. The research instrument used is collecting data in the form of questionnaires with a total of 134 respondents and using validity tests and reliability tests to test data quality, multiple linear regression analysis, and coefficient of determination testing (R2) which is used to experiment using classical assessment tests and influence tests of variables, there are also tests in the form of t-tests and f tests, namely to test hypotheses using help software in the form of SPSSversion 25. The results of the study show that : (1) There is a positive influence of service quality on purchasing decisions at Alfamidi Timoho, Yogyakarta city, as evidenced by the value of 2,702; significance value 0,008<0,05; and a regression coefficient 0f 1.978; (2) There is a positive influence of Brand Image on purchasing decisions at Alfamidi Timoho, Yogyakarta city, as evidenced by the t value 0f 4,299; a significance value of 0,000<0,05; and a regression coefficient of 1,978; (3) Promotion has a positive influence on purchasing decisions at Alfamidi Timoho, Yogyakarta city, as evidenced by the t value of 2,370; a significance value of 0,019<0,05; and a regression coefficient of 1.978; (4) There is an influence of service quality, brand image and promotion together on purchasing decisions at Alfamidi Timoho, Yogyakarta City, as evidenced by the calculated F value of 18,735 with a significance of 0,000<0,05.